New developments in international trade theoretical and empirical investigations - Katayama Seiichi ed.; RIEB International Conference on New Developments in International Trade; RIEB international conference on new developments in international trade Kobe, Japan 22-24 Mar 1998 (Kobe Kobe University, 2003)
This volume collects 14 articles that address important issues concerning or arising from trade liberization. The articles are divided into three groups. Section I gathers articles that examine various consequences of free trade. The articles in Section II investigate trade policy and trade policy formation from national and international perspectives. Section III contains three empirical examinations of the consequences of international trade.
Keywords: International trade